Peran Wisata Kuliner Dalam Pertumbuhan Ekonomi Di Destinasi Pariwisata Demak - Nur Fitriyani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Coastal processed food is one of the attractions of tourism in Demak, Demak Regency has several traditional culinary delights that have existed since royal times and must be preserved. The current of globalization causes development in an area, the culinary field is also an affected part. Culinary tourism is one of the drivers of tourists or visitors to explore a destination. In addition, culinary is also a supporting factor in reviving environmentally friendly tourism in Demak. Based on this, this study will discuss (1) How culinary tourism develops (2) Factors that influence the existence of culinary tourism with a culinary business profile in Demak (3) The function of culinary tourism in the development of economic in Demak. This research uses qualitative methods with in-depth interviews with various parties. The theories used include the theory of the five factors that influence culinary tourism and the philosophy of visitor experience. The findings of this study are (1) Demak culinary tourism is growing and diverse, namely there are several places to eat that serve Demak culinary. (2) Food processing and improve marketing can provide benefits to the surrounding economy.)